Pesantren dan Anak Jalanan : Studi Penyelenggaraan Dikterapan di Pesantren Fathul Khair Cimanggis Depok - Ta’rif Ta’rif (Badan Litbang dan Diklat Kementerian Agama RI, 2016)
This research is aimed at acknowledging the model and success level of implementation of children of hope integrated education (Dikterapan) program in Fathul Khair Islamic Boarding School, Cimanggis Depok, West Java, specifically performing development for the marginal groups. This research uses qualitative approach with the data collection techniques of in-depth interview, observation and documentation. This research results in the following findings: 1) the students participating in the children of hope integrated education (Dikterapan) program originate from the marginal groups comprising street children and orphans. They are treated equally in receiving education, nurture, food, clothing, dwelling free of charge in the relevant Islamic boarding school, 2) the students are given comprehensive materials, starting from general education, religion education, to craftsmanship education, 3) education in the relevant Islamic boarding school has successfully changed the living pattern of the street children from totally free individuals to well-organized, religious, and disciplined individuals.